B-1 Cell Immunoglobulin Directed Against Oxidation-Specific Epitopes - Tsiantoulas, Dimitrios; Gruber, Sabrina; Binder, Christoph J. (Frontiers in Immunology, 2013)
Natural antibodies (NAbs) are pre-existing antibodies with germline origin that arise in the absence of previous exposure to foreign antigens. NAbs are produced by B-1 lymphocytes and are primarily of the IgM isotype. There is accumulating evidence that – in addition to their role in antimicrobial host defense – NAbs exhibit important housekeeping functions by facilitating the non-immunogenic clearance of apoptotic cells as well as the removal of (neo-)self antigens. These properties are largely mediated by the ability of NAbs to recognize highly conserved and endogenously generated structures, which are exemplified by so-called oxidation-specific epitopes (OSEs) that are products of lipid peroxidation. The generation of OSEs as well as their interaction with the immune system have been studied extensively in the context of atherosclerosis, a chronic inflammatory disease of the vascular wall that is characterized by the accumulation of cellular debris and oxidized low-density lipoproteins (OxLDL). Both apoptotic cells as well as OxLDL carry OSEs that are targeted by NAbs. Therefore, OSEs represent stress-induced neo self-structures that mediate recognition of metabolic waste (e.g., cellular debris) by NAbs, allowing its safe disposal, which has fundamental implications in health and disease.